PENGARUH RELAKSASI BENSON TERHADAP TINGKAT KECEMASAN PADA IBU HAMIL TRIMESTER III DI PMB M 2023 - Nelli, Ermeida (Journal of Midwifery Tiara Bunda, 2022)
Background : The anxiety of pregnant women in the third trimester of pregnancy will increase as labor gets closer. Anxiety that is not controlled will have a negative impact on the mother and fetus if not addressed. This anxiety can cause premature birth, pre-eclampsia, and disruption of the birth process. One of the therapies used to reduce anxiety in pregnant women is benson relaxation therapy. This therapy produces endorphins, the production of which in the body can inhibit the activity of the central nervous system, thereby reducing the body's response to stress and anxiety Objective : : To determine the effect of benson relaxation therapy on anxiety in third trimester pregnant women at PMB M. Methods: This research is a quantitative study with a preexperimental design approach with a one-group pre-test-post-test design with pretest-posttest values of 2.13 and 1.30. The sampling technique used was accidental sampling and a sample of 30 respondents was obtained. Collecting data with observation sheets, using the HARS questionnaire (Hamilton Anxiety Rating Scale). Results: Hypothesis testing using the Wilcoxon test, obtained a significance value of 0.001 (<0.05) so that the hypothesis is accepted.